The impacts of oil price shocks on stock market volatility: Evidence from the G7 countries. (November 2016) - Bastianin, Andrea; Conti, Francesca; Manera, Matteo
Abstract: We study the effects of crude oil price shocks on the stock market volatility of the G7 countries. We identify the causes underlying oil price shocks and gauge the impacts that oil supply and oil demand innovations have on financial volatility. We show that stock market volatility does not respond to oil supply shocks. On the contrary, demand shocks impact significantly on the volatility of the G7 stock markets. Our results suggest that economic policies and financial regulation activities designed to mitigate the adverse effects of unexpected oil price movements should be designed by looking at the source of the oil price shocks. Highlights: Effects of oil price shocks on the stock market volatility of the G7 countries. Econometric identification of the different causes of oil shocks. Stock market volatility does not respond to oil supply shocks. Demand shocks impact significantly on stock market volatility. Policy measures should be designed by considering the source of oil shocks.